A COMPARISON OF TELEMEDICINE IN INDONESIA AND MALAYSIA: A LEGAL AND POLICY REVIEW - Rizka Erlyani; Handar Subhandi Bakhtiar; Muthia Sakti (Pojok Publisher, 2025)
This study aims to provide a comparative analysis of the regulatory frameworks governing digital health platforms for telemedicine services in Indonesia and Malaysia. By examining the legal structures, challenges, and opportunities in implementing telemedicine through private digital platforms, the study identifies key differences and similarities between the two countries. The study uses a normative legal approach, combining legislative analysis and comparative law. The study evaluates relevant laws and regulations in both countries, including Law No. 17 of 2023 concerning Health in Indonesia and the Telemedicine Act 1997 in Malaysia. The analysis focuses on platform-based models, such as Halodoc in Indonesia and BookDoc in Malaysia, to assess regulatory compliance, data protection measures, and their implications for healthcare access and patient safety. The findings reveal significant regulatory gaps in Indonesia, particularly regarding legal recognition of private platforms and unclear accountability mechanisms. In contrast, Malaysia's more integrated regulatory framework facilitates smoother collaboration between the public and private sectors. The study concludes with recommendations for policy improvements in Indonesia, emphasizing the need for clearer regulations to ensure legal certainty, patient protection, and service quality in telemedicine practices.